Of criteria and perceptions a study of web resource evaluation by the undergraduate students of the University of the Philippines Los Baños - Cervantes, Nicolo Lorenzo T. (2010)
This study focused on the perception of the undergraduate students of the University of the Philippines Los Baños on how they evaluate and perceive the quality of information they get from Web resources. A total of 340 students of English 2, an English composition class were surveyed. The subject was chosen as it would require students to produce a research paper. A questionnaire was used for the survey, which was extensively modified from Judd, Farrow and Tims's 2006 website evaluation form. It asked among others, their general opinion of the Internet as a research tool, their usage of different criteria for determining quality of information, and their perception of the information quality of different kinds of websites.